'The myth of integrating local knowledge': Living and ideological landscapes on Palawan Island, the Philippines - DARIO NOVELLINO (Journal of Political Ecology)
The integration of Indigenous Knowledge and perspectives into landscape protection and management schemes has now become one of the key mainstream approaches in political ecology of conservation, often referred to as 'decolonizing conservation.' Within the regional context of Palawan (the Philippines), this article looks at the play of power and knowledge that is deeply embedded in current discourses aiming at 'integrating local knowledge' into landscape governance. More importantly, it argues that such an 'integration', often builds upon a series of misunderstandings which arise spontaneously – or are intentionally fostered – between community members and project planners, due to different cognitive structures, background knowledge, languages, events and attitudes. In framing my argument, I introduce the analytical notion of 'ideological' landscape' to refer to those contrasting views of nature/society relations, which are being negotiated and strategically deployed, if and when needed. The final contention here is that one should move away and beyond simplistic approaches based on the 'integration of local knowledge' and focus, instead, to the analysis of people's counterstrategies to hegemonic nature conservation discourses.